Analysis of Air Preheater Effectiveness using The Number Transfer Unit (NTU) Method Before and After Overhaul of Unit 2 of The West Java Palabuhan Ratu PLTU - Fitriyani, Elsa; Nurhilal, Otong; Setianto, Setianto (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2026)
The air preheater (APH) is a heat exchanger component that plays a crucial role in improving boiler combustion efficiency through the reuse of hot exhaust gases. Continuous use of the APH at the Jabar 2 Palabuhan Ratu PLTU can lead to a decline in performance, characterized by reduced heat transfer effectiveness. To restore APH performance, an overhaul was performed, including cleaning and replacing the elements. The analysis was based on actual operating data by comparing pre- and post-overhaul conditions at nearly equivalent loads using the NTU-effectiveness method, as well as calculating the effect of O₂-based air leakage. The results showed that the overhaul improved the APH's performance. Under pre-overhaul conditions with a load of 333.86 MW, the effectiveness value was 85.04%, increasing to 87.72% at a load of 329.75 MW after the overhaul. At a load of 336.98 MW, the effectiveness increased from 85.68% to 87.30% at a load of 346 MW after the overhaul. At a load of 284.33 MW, the effectiveness increased from 85.82% to 87.10% at a load of 282.99 MW after the overhaul. Furthermore, the air leakage value decreased from 13.54% to 11.47% after the overhaul.